Ontology as a respective dialectics. An outline of the problem of truth and falsehood in Plato’s dialogue Sophist - Bańka, Jakub Sebastian (Folia Philosophica, 2001)
The author departs from a reminder that despite the excellent theoretical tradition in expressing the truth it still evades our expression. In order to restore the notion of truth the author suggests to abandon the Aristotelian metaphysics of substance and shift toward Plato's metaphysics of subsistence. The basis of this operation should be the analysis of Plato's dialogue titled Sophist. Instead of the absolute expression the author proposes the so called respective expression - i.e. an expression through reference “to another”. The author thinks that the dialectic procedure presented in Sophist reveals the respective structure of cognition within which the reciprocal, reflexive references and connections of ideas make possible both thinking and speech. From that moment being is no longer considered “for itself" but “in relation to another”. Translating the essence of such a capturing of the problem into the language of contemporary metaphysics the author arrives at the conclusion that the nature of the eidetic ontological structure has a respective character.